Exploring the enzymatic activity of depolymerase gp531 from Klebsiella pneumoniae jumbo phage RaK2 - Algirdas Noreika; Jonita Stankevičiūtė; Rasa Rutkienė; Rolandas Meškys; Laura Kalinienė (Virus Research, 2023)
Klebsiella pneumoniae poses a major global challenge due to its virulence, multidrug resistance, and nosocomial nature. Thus, bacteriophage-derived proteins are extensively being investigated as a means to combat this bacterium. In this study, we explored the enzymatic specificity of depolymerase gp531, encoded by the jumbo bacteriophage vB_KleM_RaK2 (RaK2). We used two different methods to modify the reducing end of the oligosaccharides released during capsule hydrolysis with gp531. Subsequent acidic cleavage with TFA, followed by TLC and HPLC-MS analyses, revealed that RaK2 gp531 is a β-(1→4)-endoglucosidase. The enzyme specifically recognizes and cleaves the capsular polysaccharide (CPS) of the Klebsiella pneumoniae K54 serotype, releasing K-unit monomers (the main product), dimers, and trimers. Depolymerase gp531 remains active from 10 to 50 °C and in the pH 3–8 range, indicating its stability and versatility. Additionally, we demonstrated that gp531′s activity is not affected by CPS acetylation, which is influenced by the growth conditions of the bacterial culture. Overall, our findings provide valuable insights into the enzymatic activity of the first characterized depolymerase targeting the capsule of the clinically relevant K54 serotype of K. pneumoniae.